Solvent-Free Extrusion Emulsification Inside a Twin-Screw Extruder - Ivancic, Tomislav (My University, 2019)
Solvent-free extrusion emulsification (SFEE) is a novel emulsification technology that operates without solvent to produce sub-micron sized particles (100–200 nm) using a twin-screw extruder (TSE) with high viscosity polymers (up to 600 Pa.s has been tested to date) and only water as the liquid medium. Surfactants have always been known to play a key role in the success of the SFEE process, however very little work has been done to investigate the mechanisms by which they operate, along with isolating the region of the process to which they play the most vital role. The first part of this thesis focused on an investigation into how different surface-active properties impacted the mechanism of SFEE. Three ionic (SDBS, Unicid 350, Calfax DB-45) and three non-ionic surfactants (Igepal CO-890, Brij 58, Synperonic F-108), each with differing surface-active properties were tested in solvent emulsification (SE) prior to their evaluation in SFEE. Synperonic F-108 was the only surfactant found unsuccessful in the SE process, and was therefore disregarded prior to SFEE testing. Of the three ionic surfactants, SDBS and Calfax were the only ones found to successfully create a stable emulsion in SFEE; the latter species doing so with 50% reduced molar loading. Igepal and Brij were found to produce very low amounts of emulsified material (5-25% of the total solids mass), requiring molar loadings that greatly exceed those of SDBS and Calfax to do so. Particles generated by both SE and SFEE were tested at extreme operating conditions to compare their relative stabilities, and were found to experience similar stability behaviours. This result reinforces previous findings that the dispersion stage controls the SFEE technique. The second part of this thesis continued the investigation on the use of non-ionics in SFEE, with a focus on the impact of their molecular structure on the overall process. Non-ionic surfactants with varying hydrophilic end group chain lengths were tested in SFEE, and it was determined that the optimal hydrophilic chain length was between 10–12 ethoxy units, where shorter chains resulted in coarse particle generation. The structure of the hydrophobic end group was tested as well, and through experimentation it was determined that a branched end group structure was slightly more beneficial than a linear end group to emulsion stabilization. As seen in the first part of this thesis, none of the new selection of non-ionic surfactants were capable of inducing sufficient phase inversion to result in a high percentage of emulsion leaving the extruder. The most promising ionic surfactant, Calfax DB-45, was combined with various promising non-ionic surfactants to create binary surfactant mixtures, and were tested in SFEE. Initial results yielded the most promising blend as Calfax/Igepal CA-630. After manipulation of both molar ratio and total surfactant loading, it was determined that a minimum Calfax loading of 0.06 mmol/g resin was required in the blend to achieve a stable 100 – 200 nm emulsion in both SE and SFEE processes, regardless of non-ionic concentration. The benefits of adding a non-ionic surfactant in the blend were seen with the substantial reduction of Calfax entrapped in the final latex particles, apparent by the distinct decrease in overall particle charge. A mini-study examining the impacts of increasing the viscosity of the water phase by hydrocolloid addition for the dilution stage has shown that positive changes to emulsion properties can be seen by this approach, but further experimentation is required before concrete conclusions can be made.
Keywords: Emulsification, Phase-Inversion, Surfactants, Twin-screw Extruder, Nanoparticles, Polyester